2021
DOI: 10.3390/jfmk6010012
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Urinary Incontinence among Adolescent Female Athletes: A Systematic Review

Abstract: This review aimed to synthesize the most up-to-date evidence regarding the prevalence of urinary incontinence (UI) among adolescent female athletes. We conducted a systematic review of studies regarding UI in female athletes less than 19 years of age. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRIMSA). The electronic databases of PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and Web of Science (WOS) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…For instance, populationbased studies carried out in women of around the same age as our participants revealed a prevalence ranging from 6 % [20] to 42.5 % [21]. Altogether, our results indicate that CrossFit® athletes show a moderate prevalence rate that somehow falls between athletes with low percentages, such as those practicing cycling (10 %) or swimming (15 %), and sports that involve impact with the ground such as volleyball (57.5 %), gymnastics (61 %) or trampoline (>80 %) [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…For instance, populationbased studies carried out in women of around the same age as our participants revealed a prevalence ranging from 6 % [20] to 42.5 % [21]. Altogether, our results indicate that CrossFit® athletes show a moderate prevalence rate that somehow falls between athletes with low percentages, such as those practicing cycling (10 %) or swimming (15 %), and sports that involve impact with the ground such as volleyball (57.5 %), gymnastics (61 %) or trampoline (>80 %) [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…Findings from meta-analyses on female athletes have pointed out a weighted average of 26–36% of UI prevalence [ 5 , 13 ]. According to the data obtained in the present review, CrossFit seems to exhibit a moderate prevalence rate that somehow falls between sports with low percentages such as cycling (10%) or swimming (15%) and high-impact modalities such as volleyball (57.5%), gymnastics (61%) or trampoline (>80%) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 92%
“…Urinary incontinence may cause embarrassment and affect performance and quality of life [ 11 ]. It can also discourage people from participating in sport and exercise [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of recent systematic reviews concerning PFD in female athletes [9][10][11][12][13][14]. However, the main aim of these reviews has been the investigation of the prevalence of UI in female athletes.…”
Section: Introductionmentioning
confidence: 99%